Risk factors for cervical cancer and adherence to papanicolaou among nursing workers - Diógenes, Maria Albertina Rocha; Cesarino, Maria Cecília Freitas; Jorge, Roberta Jeane Bezerra; Queiroz, Ingrid Nepomuceno Bezerra; Mendes, Raquel Silveira (Rev Rene, 2012)
The objective of this work was to verify the presence of risk factors for cervical cancer and identify adherence to Pap smears in nursing auxiliary and technicians to 20 primary health care, in Fortaleza, Brazil. A descriptive study was conducted from October 2008 to January 2009, involving 77 women. Data were collected using a structured interview, available on tables and treated with absolute and relative frequency. It was Shown that 71.43% of the Women were using oral contraceptives, 19.48% smoked or had smoked, 61.04% had first intercourse between 15 and 20 years of age, 77.92% did not make systematic use of condoms, 22.07% knew the importance of the examination and 84.40% would do so every year. Most joined the regular gynecological exam, but some had risk factors for cervical cancer. It is emphasized the need for an educational intervention directed at these women.